Pengembangan Bahan Ajar IPA Bermuatan Etnosains pada Materi Sistem Pencernaan Manusia Kelas 5 di Gugus 1 Prima Bakti - Widiya Restu Putri; Moh. Irawan Zain; Mansur Hakim (Mataram University, 2026)
The integration of local wisdom into primary school science education serves as the primary foundation for developing ethnoscience based teaching materials for human digetive system. This study aims to develop ethnoscience-based science teaching materials for the human digestive system for grade 5 in Gugus 1 Prima Bakti. The type of research used is Research and Development (R&D), with the model used is Analysis, Design, Development, Implementation, Evaluation. Data collection was carried out using a questionnaire given to validators of material experts, media, teachers and students. Data were analyzed qualitatively and quantitatively using a scoring table and the percentage of validity and practicality. The results showed that the developed teaching materials met the criteria of very valid with a score of 92% from material experts and 84% from media experts. The practicality test showed a positive response from both teachers and students, with a score of 94% from teachers and 88% from students on a small scale. Then on a large scale 88% from teachers and 92% from students. These results indicate that the teaching materials are suitable to use in 5th grade of elementary school and are able to increase students enthusiasm in science learning in elementary school.